1999
DOI: 10.1007/s001270050163
|View full text |Cite
|
Sign up to set email alerts
|

Social phobia in the general population: prevalence and sociodemographic profile

Abstract: Although the exact diagnostic boundaries for social phobia are difficult to determine, it can be concluded that social anxiety is a distressing problem for a considerable proportion of the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
231
4
11

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 295 publications
(266 citation statements)
references
References 22 publications
20
231
4
11
Order By: Relevance
“…The 12-month prevalence rate (4.8%) in the present study was rather lower than the previous findings (6.7-7.9%) conducted in Norway, Canada and United States of America which used DSM-III-R criteria and the CIDI [11,17,21,24]. This may be clarified by two explanations.…”
Section: Discussion J Epidemiological Resultscontrasting
confidence: 90%
See 2 more Smart Citations
“…The 12-month prevalence rate (4.8%) in the present study was rather lower than the previous findings (6.7-7.9%) conducted in Norway, Canada and United States of America which used DSM-III-R criteria and the CIDI [11,17,21,24]. This may be clarified by two explanations.…”
Section: Discussion J Epidemiological Resultscontrasting
confidence: 90%
“…The weighting procedures have been described in more detail elsewhere [5]. Furthermore, because earlier research has shown that several demographic variables are associated with social phobia, we adjusted for demographics in all analyses [8,11,16].…”
Section: J Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Esse dado reforça os achados prévios da literatura 2,5,6 de que o medo de falar em público é um domínio bastante relevante do TAS, sendo capaz de por si só, com alto grau de significância, diferenciar os sujeitos classificados como casos e não casos de TAS. Por outro lado, a capacidade da SSPS em identificar as diferenças entre os sexos, diferenças essas descritas na literatura prévia, em que as mulheres apresentam maior nível de sintomatologia em relação aos homens 29 , foi limitada e específica à subescala negativa quando da avaliação da população geral de universitários.…”
Section: Discussionunclassified
“…No transtorno de ansiedade social (TAS), que se caracteriza pelo medo e evitação de situações sociais e de performance, o falar em pú-blico também tem sido apontado como o medo mais prevalente nos portadores de TAS generalizado e, principalmente, nos portadores de TAS circunscrito ou não generalizado [4][5][6] , salientando a importância do componente cognitivo na etiologia desse transtorno.…”
Section: Introductionunclassified